The Impact of Nutritional Supplementation in Selected Chronic Medical Conditions: A Review - Chodkowski, Jakub (Quality in Sport, 2024)
Introduction: Nutritional supplementation has become an integral part of managing chronic medical conditions, offering potential benefits in improving patient outcomes and quality of life. This review explores the evidence supporting the role of dietary supplements in selected chronic conditions, including cardiovascular disease, diabetes, osteoporosis, and inflammatory disorders, while highlighting potential risks and limitations. Materials and Methods: A systematic review of peer-reviewed literature was conducted using databases such as PubMed, Scopus, and Google Scholar. Studies published between 2010 and 2023 were included if they examined the clinical impact of supplements like omega-3 fatty acids, vitamin D, calcium, chromium, and curcumin. Meta-analyses, randomized controlled trials, and observational studies were prioritized. Data extraction focused on efficacy, safety, and recommended dosages. Results: Evidence suggests that omega-3 fatty acids reduce inflammation and improve lipid profiles in cardiovascular patients. Vitamin D and calcium significantly enhance bone mineral density in osteoporosis. Chromium and alpha-lipoic acid demonstrate modest improvements in glycemic control for diabetes. However, concerns about supplement overuse, potential drug interactions, and variability in product quality persist. Conclusions: While supplementation offers therapeutic benefits in managing specific chronic conditions, its efficacy depends on patient-specific factors, including baseline nutrient status and disease severity. Clinicians must adopt an evidence-based approach, ensuring personalized recommendations and emphasizing the importance of quality control in supplementation practices. Further research is needed to clarify long-term effects and optimal dosages.